Protein folding mediated by trigger factor and Hsp70: new insights from single-molecule approaches - Wruck, Florian; Mayer, Matthias P.; Kramer, Günter (Journal of molecular biology, 2018)
Chaperones assist in protein folding, but what this common phrase means in concrete terms has remained surprisingly poorly understood. We can readily measure chaperone binding to unfolded proteins, but how they bind and affect proteins along folding trajectories has remained obscure. Here we review recent efforts by our labs and others that are beginning to pry into this issue, with a focus on the chaperones trigger factor and Hsp70. Single-molecule methods are central, as they allow the stepwise process of folding to be followed directly. First results have already revealed contrasts with long-standing paradigms: rather than acting only “early” by stabilizing unfolded chain segments, these chaperones can bind and stabilize partially folded structures as they grow to their native state. The findings suggest a fundamental redefinition of the protein folding problem and a more extensive functional repertoire of chaperones than previously assumed.
Published online: 11 September 2017
Gesehen am 15.10.2018